The impact of the COVID-19 pandemic on the mental health of women seeking treatment for postpartum depression. (12th December 2022) - Chang, Oswin; Layton, Haley; Amani, Bahar; Merza, Donya; Owais, Sawayra; Van Lieshout, Ryan J.
Abstract: Background: While research has examined the mental health of general population samples of postpartum women during the COVID-19 pandemic, the pandemic's impact on women seeking treatment for postpartum depression (PPD) is not well known. This study compared levels of depression and anxiety, the quality of social relationships, and the temperament of infants of treatment-seeking mothers in Ontario, Canada prior to and during the pandemic. Methods: Mothers with Edinburgh Postnatal Depression Scale scores ≥10 and seeking treatment for PPD prior to COVID-19 ( n = 100) were compared to those who sought treatment during the pandemic ( n = 120). Mothers self-reported symptoms of depression, worry/anxiety, partner relationship quality, social support, as well as aspects of the mother–infant relationship and infant temperament. Results: There were no statistically significant differences in symptoms of depression, anxiety, or the quality of social relationships between women seeking treatment for PPD before or during the pandemic. However, mothers reported poorer relationships with their infants, and there was evidence of more negative emotionality in their infants during COVID-19. Conclusions: The pandemic may not have worsened depression, anxiety, relationships with partners, or social support in mothers seeking treatment for PPD, but appears to have contributed to poorer mother–infant interactions and maternal reports of more negative emotionality in their infants. These findings highlight the importance of identifying women with possible PPD, supporting mother–infant interactions, and monitoring their infants during COVID-19 and beyond.